Determination of stress-bulk modulus in the lithosphere and the peak particle velocity with regards to sediment-hosted disseminated gold deposit (2017)
The tectonic activities happening within the subsurface has led to a huge trapped pressure within the plate boundaries looking for escape through the weakest points to the surface. This has led to deformation in the lithosphere which was greatest at the plate boundaries. In recent time, sediment-hosted disseminated gold deposits had been an important ore mineralization. From research it was suggested that gold, a material from subsurface derived from the core-mantle region passes through different regions of different densities, pressures and temperatures. Bulk modulus, an important parameter determined from the thermodynamic properties was investigated to the depth of the lithosphere. The ground movement was also determined with a view to ascertain the save distance and precautions when handling explosives as tools in underground mining.